Sosialisasi Kesehatan Gizi Dalam Mengoptimali Tumbuh Kembang Anak Dalam Parenting - Barus, Nadila; Chintya, Risma; Sari, Siti Erlina; Sit, Masganti (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2024)
This writing aims to train PAUD teachers and guardians of PAUD students to provide education, care and be able to maximize children's growth and development by improving nutrition for children, especially in early childhood. This research method is quantitative as is the library method as reference material in writing this article and several other scientific works. Next, the service team provided opportunities for teachers and parents to ask questions and consult with resource persons. The implementation method is in the form of socialization in the RA environment as well as material about child nutrition regarding development and growth in early childhood through parents and teachers. Our hope is that after implementing this service, teachers and parents will care more about children's growth and development so that it runs optimally. Teachers and guardians of students are also able to carry out the best care for their children according to the teachings of the Islamic religion so that children's rights are fulfilled. Providing proper nutrition and care will later help government programs to eradicate stunting in Indonesia.